2017
DOI: 10.1002/pssa.201700263
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of helium clustering in mono‐, di‐, and hexa‐vacancy in silicon

Abstract: Combining classical molecular dynamics and first-principles DFT calculations, we perfom an extensive investigation of low energy configurations for He n V m complexes in silicon. The optimal helium fillings are hence determined for V 1 , V 2 , and V 6 (figure on the right), and the structures formed by helium atoms arrangements in the vacancy defect are analyzed. For V 1 and V 2 , the He atoms structure is mainly controled by the host silicon matrix, whereas a high density helium packing is obtained for V 6 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…2) E f (n, p) is the energy needed to insert p interstitial He atoms into a cavity of n vacancies. Recent investigations revealed that the variation of this term as a function of p is quadratic [59], for a given n. We can then writẽ E f (n, p) = a(n) p 2 + b(n) p (A.3) a(n) and b(n) are calculated for all simulated bubbles with n > 10. We find that both coefficients can then be fitted by the respective expressions This expression is used for bubbles of at least 11 vacancies, or containing at least 21 helium atoms.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…2) E f (n, p) is the energy needed to insert p interstitial He atoms into a cavity of n vacancies. Recent investigations revealed that the variation of this term as a function of p is quadratic [59], for a given n. We can then writẽ E f (n, p) = a(n) p 2 + b(n) p (A.3) a(n) and b(n) are calculated for all simulated bubbles with n > 10. We find that both coefficients can then be fitted by the respective expressions This expression is used for bubbles of at least 11 vacancies, or containing at least 21 helium atoms.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ẽ f (n, p) is the energy needed to insert p interstitial He atoms into a cavity of n vacancies. Recent investigations revealed that the variation of this term as a function of p is quadratic [59], for a given n. We can then write The formation energy (in eV) of a bubble formed of n vacancies and encompassing p helium atoms is then obtained as This expression is used for bubbles of at least 11 vacancies, or containing at least 21 helium atoms. Otherwise, the binding energies are directly calculated from atomistic data.…”
Section: A2 Extrapolation At Large Sizesmentioning
confidence: 99%